Screening Motives among Attendants of Breast Cancer-Early Detection Clinics, in Iraq - Marwah Imad Al Ameen1, Khalid Kareem Rajab2, Besmah Mohammed Ali3, Jawad Kadhim Al Diwan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objectives: The early detection model for breast cancer in Iraq is a combined program of an early diagnosis for symptomatic attendants and an opportunistic unsystematic breast clinical examination screening that mainly depend on attendants’ request. With an aim to initiate breast cancer screening program, the current study’s objective is to illustrate the prevalence and motives of screening behavior among attendants.Method: A cross sectional study was conducted for a period of three months, interviewing 500 randomly selected attendants of two breast cancer early detection clinics in Baghdad city. Data presented in frequency and percentages and analyzed by binary logistic regression, P ? 0.05 reflected a significant association.Results: The results showed that only 42 (8.4%) attended the breast clinics with screening intention. Being employed (OR= 3.198; 95% C.I.= 1.284 – 7.964; P=0.013) or a student (OR=6.605; 95% C.I.= 1.125 – 38.759; P=0.037), of high socioeconomic status (OR=2.695; 95% C.I.= 1.036 –7.012; P =0.042) and having a positive family history of breast cancer (OR= 5.17; 95% C.I.= 2.466 –10.855; P <0.001) were significant reasons for breast cancer screening.Conclusions: Reforming the health system and tackling access barriers to screening should be endorsed through applying multiple components interventions to increase women participation in the service with a special focus on the less empowered under-served ones.